THE EFFECT OF WORKLOAD AND COMPENSATION ON PERFORMANCE WITH JOB SATISFACTION AS A MEDIATING VARIABLE - Rini Rahmawati; Qori Akromin (CV. Adiba Aisha Amira, 2025)
This research is to analyze the effect of workload and compensation on performance with job satisfaction as a mediating variable (study on employees of the Rangga Ilung Class III Harbormaster and Port Authority Office, Jenamas District, South Barito Regency, Central Kalimantan Province). This research uses quantitative research methods. Data collection techniques in this research were carried out using interviews and questionnaires. Data analysis techniques were carried out using the Smart PLS 3.0 analysis tool. This research found that workload had no effect on the performance of Rangga Ilung Class III Harbormaster and Port Authority employees. Compensation affects the performance of the Rangga Ilung Class III Harbormaster and Port Authority employees. Job satisfaction has no effect on the performance of Rangga Ilung Class III Harbormaster and Port Authority employees. Workload has no effect on job satisfaction at the Rangga Ilung Class III Harbormaster and Port Authority Office. Compensation influences the job satisfaction of Rangga Ilung Class III Harbormaster and Port Authority employees. Workload has no effect on the performance of Rangga Ilung Class III Harbormaster and Port Authority employees with job satisfaction as a mediating variable. Compensation has no effect on the performance of Rangga Ilung Class III Harbormaster and Port Authority employees with job satisfaction as a mediating variable.